2022
DOI: 10.1037/bul0000359
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported mindfulness accounts for the effects of mindfulness interventions and nonmindfulness controls on self-reported mental health: A preregistered systematic review and three-level meta-analysis of 146 randomized controlled trials.

Abstract: Meta-analyses suggest that mindfulness interventions have positive effects on mental health. Yet, how mindfulness interventions exert their effects is still largely unknown. Self-reported mindfulness may partially mediate the association between mindfulness interventions and change in self-reported mental health. We present the results of a novel application of three-level meta-analysis on the pre-post intervention data of 146 RCTs of mindfulness interventions (total N = 10,979), probing the efficacy of a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 103 publications
3
10
0
Order By: Relevance
“…We hypothesize that the PSA that Group B read might promote acceptance level to some degree, leading to non-different acceptance scores between groups. A 2022 meta-analysis [47] supports our hypothesis reporting that self-reported mindfulness is nonunique to mindfulness intervention, and can be increased by non-mindfulness interventions, even in a wait-list control group that received no intervention. Another considerable possible explanation of non-different acceptance level between groups is that acceptance attitude might appear more in those who practice mindfulness for prolonged periods of time.…”
Section: Discussionsupporting
confidence: 69%
“…We hypothesize that the PSA that Group B read might promote acceptance level to some degree, leading to non-different acceptance scores between groups. A 2022 meta-analysis [47] supports our hypothesis reporting that self-reported mindfulness is nonunique to mindfulness intervention, and can be increased by non-mindfulness interventions, even in a wait-list control group that received no intervention. Another considerable possible explanation of non-different acceptance level between groups is that acceptance attitude might appear more in those who practice mindfulness for prolonged periods of time.…”
Section: Discussionsupporting
confidence: 69%
“…We hypothesize that the PSA that Group B read might promote acceptance level to some degree, leading to non-different acceptance scores between groups. A 2022 meta-analysis [ 47 ] supports our hypothesis reporting that self-reported mindfulness is non-unique to mindfulness intervention and can be increased by non-mindfulness interventions, even in a wait-list control group that received no intervention. Another considerable possible explanation of non-different acceptance level between groups is that an acceptance attitude might appear more in those who practice mindfulness for prolonged periods of time.…”
Section: Discussionsupporting
confidence: 60%
“…Yet, to the extent that MBIs do appear to increase TA, it could be used as an objective measure for the efficacy of mindfulness interventions. It could complement, or replace, more subjective self-ratings of psychometric mindfulness or mental health in this field of research (Goldberg et al, 2022;Tran et al, 2022). This needs to be addressed in future research, which also needs to investigate in more detail the exact conditions under which either high or low telomerase levels can be considered a marker for good or improved cellular health (Epel, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns regarding the risk of bias in primary studies and publication bias suggested that the current meta-analytic summary effects still may have been overestimated and the utilized search strategy may have been suboptimal in retrieving non-English studies as only the first 500 hits in Google Scholar were screened for eligibility in the second stage of the literature search. Study quality needs to be increased in this field of research (see also Goldberg et al, 2022;Tran et al, 2022) problems of available studies. Larger samples are needed to increase studies' analytic power.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation